An internal electrode strategy for enhancing the stability and durability of triboelectric nanogenerator. (26th May 2023) - Xie, Yibing; Wang, Zihao; Ren, Xiaoyue; Antwi-Afari, Maxwell Fordjour; Wang, Yameng; Mi, Hao-Yang; Yang, Bao; Liu, Chuntai; Shen, Changyu
Abstract: In this study, an internal electrode triboelectric nanogenerator (IE-TENG) design is proposed to enhance the stability, durability, and long-term performance of TENGs. By embedding a mesh-structured metal electrode in the friction layer, the IE-TENG becomes more flexible, lightweight, and robust than the traditional external electrode TENG (EE-TENG). When using copper mesh internal electrodes with higher grid density, the greater output can be achieved by comparing a series of polydimethylsiloxane(PDMS)-based IE-TENG. An equivalent output was obtained when using 60 copper mesh compared to EE-TENG, and the trend maintains for tribonegative low-density polyethylene (LDPE) and tribopositive polyamide (PA) polymers, which verifies the usability of the approach and the effective induction area of the internal electrode. The internal electrode design significantly enhanced the tolerance of the device to harsh environments and guaranteed excellent output stability. In addition, the IE-TENGs possess superior resistance to external interference and had about one time shorter saturation time for surface charges. As a demonstration, the IE-TENG can be used for collecting motion-sensing signals and detecting various sports activities. This study provides a novel strategy for the designing and customizing of highly integrated TENGs with enhanced durability for practical long-term applications. Graphical abstract: An embedded metal electrode design is proposed for developing highly integrated durable TENGs. The internal electrode TENGs (IE-TENGs) not only possess equvalent output performance to the traditional external electrode TENGs, but also demonstrate superior long-term stability, charge saturation velocity, flexibility, and tolerence to harsh environments. Image 1 Highlights: A design of embedded electrode for improving the integration of TENG is proposed. The IE-TENG demonstrated more stable long-term signals, and high tolerance to the harsh environment. The embedded electrode strategy enhanced the tolerance of the TENGs to interference from the external environment. The IE-TENGs possess about one time shorter saturation time for surface charges.